2021
DOI: 10.1053/j.jvca.2021.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Early and Midterm Clinical Outcomes of Transcatheter Valve-in-Valve Implantation Versus Redo Surgical Aortic Valve Replacement for Aortic Bioprosthetic Valve Degeneration: Two Faces of the Same Medal

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…The valve has grown in popularity mostly due to the reduced cardiopulmonary bypass (CPB) time ( 1 ), the improved myocardial recovery time and its application in minimally invasive cardiac surgery (MICS) procedures ( 2 ). In addition, the three PARTNER clinical trials' ( 3 5 ), the SURTAVI trial ( 6 ) and other observational cohort studies ( 7 , 8 ) have evidenced the non-inferiority of TAVR vs. SAVR. In this context, some reports of successful valve-in-valve TAVR in bioprostheses with structural valve deterioration (SVD) have generated enthusiasm particularly for future applications ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…The valve has grown in popularity mostly due to the reduced cardiopulmonary bypass (CPB) time ( 1 ), the improved myocardial recovery time and its application in minimally invasive cardiac surgery (MICS) procedures ( 2 ). In addition, the three PARTNER clinical trials' ( 3 5 ), the SURTAVI trial ( 6 ) and other observational cohort studies ( 7 , 8 ) have evidenced the non-inferiority of TAVR vs. SAVR. In this context, some reports of successful valve-in-valve TAVR in bioprostheses with structural valve deterioration (SVD) have generated enthusiasm particularly for future applications ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…The overall OR for operative mortality (Supporting Information: Figure ) demonstrated a statistically significant difference favoring ViV‐TAVR over redo SAVR (random‐effects model: OR: 0.37; 95% CI: 0.27–0.49; p < .001) 6,9,12,14,15,17–19,22,24 . There was no evidence of heterogeneity among studies reporting on operative mortality.…”
Section: Resultsmentioning
confidence: 90%
“…The overall OR for operative mortality (Supporting Information: Figure 8A) demonstrated a statistically significant difference favoring ViV-TAVR over redo SAVR (random-effects model: OR: 0.37; 95% CI: 0.27-0.49; p < .001). 6,9,12,14,15,[17][18][19]22,24 There was no evidence of heterogeneity among studies reporting on operative mortality. The overall OR for 30-day mortality (Supporting Information: Figure 8B) showed no statistically significant difference between ViV-TAVR and redo SAVR (random-effects model: OR: 0.92; 95% CI: 0.53-1.60; p = .78).…”
Section: Operative Mortality and 30-day Mortalitymentioning
confidence: 97%
“…Multiple previous studies have shown ViV TAVI to be a less invasive approach with noninferior to superior outcomes compared with redo SAVR, despite generally higher risk patient populations. 19 , 20 , 21 , 22 , 23 The caveat to this is that most of these studies were retrospective with limited data on long-term outcomes. Clinical trials are needed to evaluate the safety and efficacy profile of each treatment modality thoroughly.…”
Section: Discussionmentioning
confidence: 99%